PENYEBARAN KULIM (Scorodocarpus borneensis Becc.) DI CAGAR ALAM BUKIT BUNGKUK KABUPATEN KAMPAR PROVINSI RIAU - Bayu Suhendra; Defri Yoza Yoza; Viny Volcherina Darlis (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Deforestation of forest areas has a direct impact on the condition of flora and fauna, disturbed biodiversity and can lead to the extinction of certain species, one of which is kulim. Kulim is MPTS (Multipurpose Tree Species), almost all parts of the tree have high economic value, the wood is widely used by the community. The purpose of this study was to determine the distribution and characteristics of the habitat of the kulim (Scorodocarpus borneensis Becc.) In the Bukit Bungkuk Nature Reserve. The research method used is a survey method using vegetation analysis. The method of vegetation analysis in this study is a combination of the pathway and checkered line method. The results of the research that have been carried out indicate that the pattern of distribution of the skin in the Bukit Bungkuk Nature Reserve which is located on the three research lines forms a clustered distribution pattern. This is evidenced by the standard morisita degree obtained which shows Ip > 0. Kulim lives on sandy loam soils with a yellowish brown color and an average pH of 4,6 (acid). The average temperature is 26,8 °C and the average humidity is 84,9%. Other vegetation contained in the research plot amounted to 59 types with the level of seedlings, saplings, poles and trees.Keywords:Distribution pattern, habitat, kulim, Bukit Bungkuk Nature Reserve